CAN FINANCIAL INSTRUMENTS BE USED AS A SUBSTITUTE FOR REINSURANCE? - Remtulla, Mohez (Assurances, 1997)
Financial instruments such as insurance catastrophe futures contracts are an innovative and legitimate way in which capital markets can help insurers reduce the risk of catastrophic claims. Financial instruments can be designed to reduce insurance risk and used as a substitute or complement to reinsurance. However, the usefulness of reinsurance will not entirely disappear.